Formulasi Sediaan Patch dari Ekstrak Daun Salam (Syzygium polyanthum [Wight.] Walp.)dan Uji Aktivitas Antibakteri Propionibacterium acne Secara In Vitro (Indonesian Journal of Pharmaceutical and Clinical Research, 2023)
The use of S. polyanthum as an alternative to treat acne has been widely studied because it contains active substances that have antibacterial properties against Propionibacterium acne. The formulation of S. polyanthum extract into a patch preparation has many advantages. This study aimed to formulate and evaluate the physical properties of S. polyanthum extract patches, and determine their antibacterial activity against Propionibacterium acne. Patch preparations were made using the solvent casting method in 6 formulas with various polymer concentrations. Evaluation of the preparations included organoleptic tests, weight uniformity, thickness, pH, folding resistance, swelling, and turbidity. Antibacterial activity test against Propionibacterium acne was carried out on the resulting extract and patch preparations. The resulting patch provides a distinctive color and aroma of the extract, with a weight between 0.036–0.050 mm, thickness between 0.21–0.30 mm, pH between 4.43–5.06, folding power >500 folds, swelling percentage in medium phosphate buffer, pH 5.8, between 19.2%-30.8%, and distilled water between 18.8%-29.2%, and turbidity in medium phosphate buffer, pH 5.8,  between 5.50–8.16 NTU, and distilled water between 4.02–5.57 NTU. S.polyanthum extract had the largest inhibition zone at 5% concentration, namely 13.56±1.40 mm. Meanwhile, patch preparations had the greatest inhibition in F1, namely 11.31±0.175 mm. S. polyanthum extract can be formulated into patches with a concentration of 5% at various concentrations of HPMC and chitosan. Patch preparations on F1 with a comparison of HPMC : chitosan (7:3) gave the largest inhibition zone against Propionibacterium acne, namely 11.31±0.175 mm.